The variability of the Polish word stress. Antepenultimate stress - Osowicka-Kondratowicz, Magdalena (Papers in Linguistics, 2021)
The article presents the results of research on the phonetic awareness of young Poles regarding the evaluation of sound variants of selected accent doublets such as mogliśmy/ mogliśmy, logika/logika, bijatyka/bijatyka, prezydent/prezydent etc. The proposed conclusions point to a relatively good auditory discrimination of the phonetic variants of the words in question as well as differences between some of the respondents’ decisions and correctness recommendations formulated in dictionaries.